Imaging hepatic angiomyolipomas: key features and avoiding errors. Issue 2 (February 2020) - Seow, J.; McGill, M.; Wang, W.; Smith, P.; Goodwin, M.
Abstract : Hepatic angiomyolipomas (HAMLs) are rare mesenchymal neoplasms, which have highly variable imaging appearances, often leading to misdiagnosis. They belong to the family of perivascular epithelioid cell neoplasms (PEComas). HAMLs have a wide spectrum of imaging appearances due to variable amounts of smooth muscle cells, adipose tissue, and blood vessels in their makeup. Although typically sporadic, they are also associated with tuberous sclerosis. Sporadic lesions tend to be solitary whilst patients with tuberous sclerosis often have multiple HAMLs invariably accompanied by renal AMLs. Having been originally considered benign hamartomas, increasing reports of complications, including malignant behaviour, has also resulted in uncertainty in regard to their optimal management. Typically described imaging characteristics are of a hypervascular fat-containing lesion with prominent intratumoural vessels and an early draining vein; however HAMLs commonly demonstrate a paucity of fat or wash-out on contrast-enhanced imaging, and not all HAML lesions are hypervascular. HAMLs can therefore easily be misdiagnosed as other hepatic lesions, in particular hepatocellular carcinoma. This review describes the imaging characteristics of HAMLs, illustrating the wide variety of potential appearances across ultrasound, contrast-enhanced ultrasound, computed tomography, and magnetic resonance imaging, and highlights the challenges and potential errors that can be made. This review will aid radiologists in avoiding potentially major pitfalls when faced with this rare but important liver pathology. Highlights: Hepatic AMLs contain variable amounts of muscle cells, adipose tissue and vessels. Typically seen as a fat containing hypervascular lesion with early draining vein. However varying composition and paucity of adipose tissue can lead to misdiagnosis. Most often misdiagnosed as hepatocellular carcinoma. Reported malignant potential with uncertainty regarding optimal management.